Analysis of antioxidant in aqueous extracted of selected ulam using ferric reducing antioxidant power (frap) assay / Mohamad Azman Janal Abidin - Janal Abidin, Mohamad Azman (Faculty Of Applied Sciences, 2019)
Ulam refer as a fresh green salad by Malaysians and usually eaten with a bowl of rice as a side dishes. The salads are very good against some diseases and had positive effects that lies in some chemical substances inside the plants such as flavonoids and phenolic compounds that contributes to its antioxidants properties. The present study was to analyse the concentration of antioxidant in different types of selected ulam that was available at the Malaysia market using Ferric Reducing Antioxidant Power (FRAP) assay. The ulam samples were analysed by using Uv Vis spectrophotometer at wavelength 593 nm. A sample of ulam known as Anarcardium occidentade (Jambu Gajus) showed the highest antioxidant activity and the lowest was Morinda citrifolia (Mengkudu Besar). The study also was conducted to compare the amount of antioxidant content between the shoots and the leaves of the selected ulam. Based on the five samples studied, it founds that three of the samples have higher antioxidant activity at their shoots compared to the leaves. Another two have higher antioxidant activity at their leaves compared tom the shoots.